Best Answer

12x - 28 = 7x - 63

Subtract 7x from each side:

5x - 28 = -63

Add 28 to each side:

5x = -35

Divide each side by 5:

x = -7

Q: 12x-28 equals -63 plus 7x

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 24 = 9x - 39= 2x + 63 = 9x= 63 = 7x= x = 9

9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)

-46 = 3x + 7x

13x

It is 9x

Related questions

The required equation is: -7x = 63

2x + 24 = 9x - 39= 2x + 63 = 9x= 63 = 7x= x = 9

7x + 5 = 68 subtract 5 from both sides 7x = 63 divide both sides by 7 x = 9

9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)

-46 = 3x + 7x

7x + y = 8 Subtract 7x from each side of the equation: y = -7x + 8

13x

It is 9x

x=6

-7x + 5 = -9 -7x = -14 7x = 14 x = 2

7x + y = 4y = 4 - 7x

7x is still the slope, no matter what x equals.